The Influence of Service Quality, Product Quality, and Price on Customer Loyalty Through Customer Satisfaction in the Natural Materials Industry of PT Panca Nature International - Hendra Rizki Akbar; Didin Hikmah Perkasa (Fakultas Ekonomi & Bisnis Universitas Paramadina, 2025)
This study aims to analyze the Influence of Service Quality, Product Quality, and Price on Customer Loyalty Through Customer Satisfaction in the Natural Materials Industry of PT. Panca Nature International. The research method used in this study is a quantitative approach with a survey technique involving consumers of PT. Panca Nature International. The population and sample of the study were 168 people using a purposive sampling technique. Data were collected using a questionnaire designed to measure the variables of service quality, Product, Price. Customer Loyalty and Satisfaction. The data analysis technique used partial least The results of the study show: Service Quality affects Customer Satisfaction, Product Quality affects Customer Satisfaction, Price affects Customer Satisfaction, Service Quality affects Customer Loyalty, Product Quality affects Customer Loyalty, Price affects Customer Loyalty, Customer Satisfaction affects Customer Loyalty, Customer satisfaction mediates the relationship between service quality and Customer Loyalty, Customer Satisfaction mediates the relationship between Product Quality and Customer Loyalty and Customer Satisfaction mediates the relationship between Price and Customer Loyalty.